This Land Is Our Land The Struggle for a New Commonwealth. - Purdy, Jedediah (Princeton University Press, 2021)
From one of our finest writers and leading environmental thinkers, a powerful book about how the land we share divides us--and how it could unite usToday, we are at a turning point as we face ecological and political crises that are rooted in conflicts over the land itself. But these problems can be solved if we draw on elements of our tradition that move us toward a new commonwealth--a community founded on the well-being of all people and the natural world. In this brief, powerful, timely, and hopeful book, Jedediah Purdy explores how we might begin to heal our fractured and contentious relationship with the land and with each other.